Integrating Phonemic Awareness into Activity-based Oral English: Enhancing Early Literacy in Sri Lanka - Jokeswaran, V. (University of Jaffna, 2025)
This paper explores the importance of integrating phonemic awareness (PA) into Activity-Based Oral English (ABOE) for Grade 1 and 2 students at state schools in Sri Lanka. It argues that such integration would lay a vital foundation for developing reading and writing skills in Grade-3 onwards. Phonemic awareness refers to the ability to hear, identify and manipulate individual sounds in spoken words and syllables, including recognising how sounds change depending on the sounds in close proximity in a particular utterance. Currently, the ABOE approach in Grades 1 and 2 is rooted in rote memorisation of words and sentences, without emphasising the underlying speech sounds. This approach, while cognitively demanding, does not effectively prepare students for systematic reading and writing in later grades. Research shows that early difficulties in recognising and manipulating sounds within words predict later reading struggles. Developing PA helps children understand that words are made of individual sounds and that letters systematically represent these sounds. Early exposure to PA equips students with strategies to decode unfamiliar words, improving future reading skills. Inculcating phonemic knowledge in students of earlier Grades, therefore, will make them better learners as they will begin formal reading and writing from Grade-3 forth. To support this shift, students need to understand that written letters represent abstract speech sounds and be able to recognise differences and similarities in these sounds, as letter names and sounds do not always align. Through a review of existing literature on phonemic awareness, this paper demonstrates how incorporating PA into ABOE can improve students’ understanding of speech sounds, helping them better decode words, read print and grasp orthography by linking sounds to the corresponding letter or letter combinations.
Keywords: Early literacy; Speech sounds and syllables; Literacy foundation; Phonological awareness; Early education; Orthography; Sound-symbol correspondence